The Moderating Effect of Surplus Free Cash Flow on Ownership Structure Earnings Quality Relationship - Al-Dhamari, Redwhan Ahmed; Ku Ismail, Ku Nor Izah (UUM Press, 2011)
Theoretically, good corporate governance mechanisms are expected to enhance the quality of reported earnings to financial statement users. Nevertheless, some existent literature on the association between ownership structure and earnings quality in both developed and developing countries have reported inconclusive results. Thus, the objective of this study is to empirically investigate the relationship between ownership structure and earnings quality of non-financial firms listed on the Bursa Malaysia when considering free cash flow agency problem. Stock ownership by management and institutions are used to represent ownership structure. The quality of earnings is analysed through earnings persistence, earnings predictability, and earnings informative. Ownership structure, financial, and stock price data are gathered from sample firms for the years of 2008 through 2009. Pooled hierarchical regressions for each model are conducted to test the hypotheses.